Microsoft 70-412 : configuring advanced Windows Server 2012 services R2 - Sutton, Darrin; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"This course is specifically for participants to gain the knowledge and skills for making the appropriate job role decisions around configuring advanced Windows Server 2012 R2 services. This course is designed for Information Technology (IT) professionals, who have Windows Server 2012 operating system knowledge and experience and want to validate the skills and knowledge necessary to configure advanced services in a Windows Server 2012 infrastructure. This course is part three of a series of courses which validate the advanced configuring tasks necessary to deploy, manage and maintain a Windows Server 2012 infrastructure, such as fault tolerance, certificate services, and identity federation. This course, along with the others in this series, will validate the skills and knowledge necessary for implementing, managing, maintaining and provisioning services and infrastructure in a Windows Server 2012 environment."--Resource description page.
Title from resource description page (viewed April 10, 2017).
Presenter, Darrin Sutton.
Keywords: Microsoft Windows server -- Certification -- Study guides; Client/server computing -- Study guides; Electronic data processing personnel -- Certification -- Study guides; Electronic books